A Case Series of α-Thalassemia Intermedia Due to Compound Heterozygosity for Hb Adana [HBA2: c179G>A (or HBA1); p.Gly60Asp] With Other α-Thalassemias in Malay Families. (August 2014) - Alauddin, Hafiza; Jaapar, Noor-Adilah; Azma, Raja Z.; Ithnin, Azlin; Razak, Noor-Farisah A.; Loh, C-Khai; Alias, Hamidah; Abdul-Latiff, Zarina; Othman, Ainoon
Abstract Hb Adana [HBA2: c179G>A (or HBA1); p.Gly60Asp] is a rare hemoglobin (Hb) variant due to a mutation at codon 59 of the α2- or α1-globin gene resulting in a glycine to aspartic acid substitution. Two siblings with a unique coinheritance of Hb Adana and Hb Constant Spring (Hb CS, α142, Term→Gln, TAA>CAA; HBA2: c.427 T>C) (αcodon 59α/αCSα), were compared phenotypically with another two siblings carrying the Hb Adana mutation and a 3.7 kb deletion (αcodon 59α/−α3.7). Although they all had α-thalassemia intermedia (α-TI), the former were clinically more severe than the latter. The first pair of siblings presented at a much younger age than the second pair and showed lower Hb levels and significant extramedullay hemopoiesis. Another case of a hydropic fetus as a result of Hb H/Hb Adana is also described. Their clinical phenotypes and hematological parameters are all presented for comparison.